Alliances for Knowledge: MOOCs to Create New Professional Skills in a New Model of University (Positive and Negative Aspects) - Garito, Maria Amata (International Journal of Advanced Corporate Learning (iJAC), 2016)
A generational clash of enormous scope is emerging within our institutions; the criticisms to the university advanced 15 years ago were "waiting ideas’’: waiting for the new Web and for a new generation of students able to effectively put in question the old model of university. The university in the globalized and the interconnected knowledge society reached a turning point; we are at a crossroads between stagnation and renewal, between atrophy and renaissance. At present, however, there are very interesting facts going on worldwide; in some prestigious universities a new idea of global education is starting from the bottom; many universities are tearing down their ivory towers and are using the Internet, the most powerful platform in history to make their contents available in the Web. Lately, in the United States as well as in Europe, the “Knowledge Alliances” and the MOOCs (Massive Open Online Courses) are emerging. Unfortunately, The MOOCs show several shortcomings that are linked to their pedagogical-didactic models, to the courses evaluation systems as well as to the organizational models of the virtual structures meant to carry on the educational activities by using the MOOCs. Today we have to make a critical appreciation of the MOOCs in order to put them into a proper historical and cultural setting. Sharing the contents of different universities of the world can certainly represent a significant step towards renewal, however, in the universities, a true change can take place through the establishment of consortia among the various universities of the world and the technological enterprises linked to innovation that cooperate in the joint production of contents in the learning environments of the Internet.